Methadone as a First-Line Opioid in Cancer Pain Management: A Systematic Review - Mercadante, Sebastiano; Bruera, Eduardo (Journal of pain and symptom management, 2018)
The objective of this review was to assess the existent evidence for the use of methadone as a first-line therapy in cancer pain management. A systematic literature search on MEDLINE and Embase databases was carried out from each database, setting up the date to August 30, 2017. Studies were included if methadone was a first-line drug as a Step 3 of World Health Organization analgesic ladder, or at low doses (Step 2), if they were conducted in adult patients with cancer pain, and if they contained outcomes on pain- and opioid-related adverse effects. The initial search yielded 219 records. Ten articles were considered after the initial screening according to inclusion and exclusion criteria. They included three longitudinal open-label studies. In two studies methadone was initiated at low doses (≤10 mg/day). These studies suggested that methadone was effective in providing analgesia and well tolerated as first opioid at different starting doses and in different conditions and settings. Five additional studies were randomized controlled studies with morphine in patients who had received opioids for moderate pain. Methadone, compared with oral morphine, or transdermal fentanyl, either at low (Step 2 level) or relatively higher doses (Step 3 level), provided similar analgesia with similar adverse effects profile with limited dose escalation in time. Available data are not sufficient to draw net conclusion. However, open-label and controlled studies have shown that methadone may be effective as first-line drug in the management of cancer pain, providing analgesia and adverse effect profiles similar to those produced by other opioids. The finding that methadone doses tend to remain stable suggests that metabolic characteristics and extraopioid analgesic effects, as its well antihyperalgesic properties may be interesting potential advantages. Further studies should provide information regarding the long-term use of methadone or the need to switch from methadone to other opioids when a loss of analgesic response occurs.